A Novel Management of Vertical Root Fracture in an Endodontically Treated Mandibular Premolar with Titanium Screw: A Case Report - Chellaswamy Savrimalai Karumaran; M. R. Srinivasan; Anil Kumar Ramachandran; Remya Venkatesan; Chandrasekaran Nirmala; P.S. Sreelakshmi (Indian Journal of Dental Research)
Introduction: Vertical root fracture is one of the conditions prevalent in endodontically treated teeth. The treatment options include extraction of the fracture fragment or the affected tooth as a whole. This case report highlights the successful management of vertical root fracture in an endodontically treated mandibular first premolar. Method: Surgical intervention was initiated, and a full-thickness flap was elevated. The separated fracture segment was safely retrieved, and the existing caries were removed and then reattached to the main fragment with the help of a titanium screw. The tooth was rehabilitated with a composite resin core followed by a porcelain-fused metal crown and the patient was followed up for 7 years. Result: The tooth was functional with evidence of new bone formation. Conclusion: Reattachment of the fracture fragments with a titanium screw might be considered as an option for managing vertical root fracture cases with poor prognosis.